Familial biatrial cardiac myxoma with glandular elements: A Rare entity with review of literature - Devajit Nath; Sudheer Arava; Ruma Ray; Amol Kumar Bhoje; Rachit Saxena; Shiv Kumar Chaudhary (Wolters Kluwer Medknow Publications, 2017)
Cardiac myxomas are benign neoplasm of the heart with an incidence of 0.3%. Glandular cardiac myxomas are very rare and accounts for less than 3% of all cardiac myxomas. Here, we report a case of familial glandular cardiac myxoma in a 35 year old male who complained of exertional dyspneoa and weakness of right side of body on clinical presentation. Associated features of Carney's complex were not present. Family history revealed presence of cardiac myxoma in younger brother and sister. Transthoracic echocardiography detected biatrial myxoma. Excision of both lesions was done under cardiopulmonary bypass. Histopathology confirmed myxoma with glandular elements. Postoperative course was uneventful.